Team Games Tournaments Learning Model Assisted by Question Cards on Improving Critical Thinking Skills - Regina Widyadhari, Clorinda; Budi Santosa, Agus; William, Nanda (EduStream: Jurnal Pendidikan Dasar, 2024)
Critical thinking is important to be honed and improved. The purpose of this study is to measure the influence of the learning model of Team Games Tournaments (TGT) assisted by media question cards on the improvement of critical thinking skills of fourth grade elementary school students. This research method uses a quantitative approach with a quasi experiment method which is a non-equivalent control group design. This research involves a control class and an experimental class. The control class consisted of 21 students and the experimental class consisted of 31 students. The data collection technique in this study is in the form of a test with a test question instrument. The data analysis used is the Mann Whitney test. The results of the analysis obtained a significance value of 0.00 which is smaller than the probability of 0.05 so that there is a difference between the control class and the experimental class. From the comparison of pretest and posttest results, the difference in pretest and posttest scores in the experimental class was higher than in the control class. In conclusion, there is a significant influence in the use of the Team Games Tournaments learning model assisted by question cards on improving the critical thinking skills of fourth grade elementary school students.